Architecture for diverse modulation techniques in SDR. (13th February 2019) - Savitha, G.; Karthikeyan, S.
Summary: Software defined radio (SDR) technology supports multiple air interfaces and modulation formats for wireless devices, which is vital when paralleled with the proliferation of wireless standards. To achieve such flexibility and functionality, SDR uses Field Programmable Gate Array (FPGA) with reconfigurable fabric. In the proposed work, different modulation techniques available in SDR are presented. Design and implementation procedure on Xilinx FPGA are also discussed. The VHDL hardware description language is used for designing and implementing the various modulators. The Xilinx EDA tool is used to synthesize the proposed one. The reconfiguration of bits is used to select the various modulation techniques dynamically with the help of Xilinx software. This proposed design makes the implementation of SDR based modulators very simple and fast.